Prevalence of hepatitis B and vaccination response in patients with end-stage kidney disease on dialysis at a tertiary centre in the Eastern Cape province of South Africa - Mtingi-Nkonzombi, Lungiswa; Manning, Kathryn; Ensor, Jason; Surdut, Samuel; Gigi, Nkululo; Walton, Noel; Freercks, Robert (African Journal of Nephrology, 2022)
Introduction: Hepatitis B virus (HBV) infection remains a concern in dialysis populations where vaccination has been less successful than in the general population. Possible reasons for poor response to vaccination in this population include malnutrition, age, uraemia, dialysis vintage, human immunodeficiency virus (HIV) infection and the generalized immunosuppressive state of patients with chronic kidney disease (CKD). Methods: This retrospective point prevalent cohort study evaluated the prevalence of HBV infection in a dialysis population at a tertiary centre in South Africa where there is a high prevalence of HIV. In addition, antibody responses following natural HBV infection versus vaccination were examined in the same population as well as factors that may affect the HBV vaccination antibody response. Results: There were 107 study participants. The prevalence rate of chronic HBV was high at 6.5% (n = 7), whereas 48 (45%) patients demonstrated evidence of HBV exposure. Patients with naturally acquired immunity demonstrated a more robust and sustained antibody response over the study period, whereas booster dose(s) were required to achieve similar levels of protection in the vaccinated group. Only one (2.1%) of those requiring vaccination never achieved an adequate seroprotection response to vaccination at any time point during the study period. Older age was the only factor shown to reduce seroconversion after primary vaccination. Despite high HIV prevalence (23%), HIV status did not affect antibody response to vaccination. Conclusion: We therefore conclude that in a cohort of dialysis patients with high HBV prevalence, natural immunity provides sustained and adequate protection. HBV vaccination in this dialysis cohort was successful, but additional booster doses were frequently required to achieve adequate seroprotection, regardless of HIV status.